Perancangan Jig & Fixture Press Tool Pada Mesin Press Bending PPBL 70/25 Di Laboratorium Teknologi Produksi Universitas Riau - Wahyu Yustyanto; Herisiswanto Herisiswanto; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Press tool is a tool to produce a component in bulk with the same shape and size, so that it becomes the desired production item. Jigs and fixture is a tool that holds a production workpiece, which can be the doubling of components accurately. This research aims to connect the two devices, jigs and fixture is needed as a link between the top and bottom positions of the press tool and to grip the workpiece so it doesn't move when the production process is being carried out. The use of a bending press machine as a pressing force on the press tool so that it can produce in large quantities in a relatively short time, the work area of a large bending press is 2500 mm x 140 mm x 300 mm, allowing many press tools to be joined by press bending, because jigs and fixture only measures 300 mm x 250 mm x 300 mm. The parts of jigs and fixture are top position, bottom position, and dies. The method used the finite element using inventor software to determine the voltage, deflection and safety factors of jigs and fixture. From the results of manual calculation, it was found that the force needed to cut a 2 mm thick plate of 160 Kn. From the results of the inventor analysis for the upper and lower plates obtained the maximum voltage of 33.8 MPa and 67.28 MPa, deflection of 0.01513 mm and 0.01284 mm, safety factor of 15.Keyword : Jigs, Fixture, Press Tool, Press Bending, Autodesk Inventor